The influence of transformational leadership style, competency and emotional intelligence on job stress, job satisfaction and performance of women leaders of private universities (PTS) in LLDIKTI region VII, which is moderate by work-life balance - Prameswari, Riski Dwi; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2024)
This research aims to examine the influence of transformational leadership style, competence, and emotional intelligence on job stress, job satisfaction, and performance of women leaders, which are moderated by work-life balance. Using a quantitative approach with explanatory research as the object of study using SEM-PLS analysis. The sampling technique used was simple random sampling, and a sample of 78 respondents was obtained. Data collection techniques were carried out using observation, interviews and questionnaires. The results are transformational leadership style has a negative and significant effect on work stress, transformational leadership style has a positive and significant effect on job satisfaction, transformational leadership style has no significant effect on individual performance, competence has a negative and significant effect on work stress, competence has a positive and significant effect on job satisfaction, competence has a positive and significant effect on individual performance, emotional intelligence has a negative and significant effect on work stress, emotional intelligence has a positive and significant effect on job satisfaction, emotional intelligence has no significant effect on individual performance, work stress has a negative and significant effect on individual performance , job satisfaction has a positive and significant effect on individual performance, work-life balance strengthens the negative influence of work stress on individual performance and work-life balance weakens the positive influence of job satisfaction on individual performance.